Non-perturbative corrections from an s-channel approach - Hautmann, F (Verlag Deutsches Elektronen-Synchrotron, 2009)
We report on studies of multi-parton corrections from nonlocal operator expansion. We discuss relations between eikonal-line matrix elements and parton distributions, and present an illustration for initialstate collinear evolution.